Identifikasi Kesulitan Belajar Tematik Kelas 3 di SD Negeri 14 Tangerang - Ina Magdalena; Tiara Safitri; Nurlaili Maghfiroh; Niken Nur Yolawati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
Regulation of the Minister of National Education No. 41 of 2007 hinted at the use of thematic approach in the learning of grade 1 to grade 3 of elementary school (SD). Even today after the implementation of the 2013 curriculum, the thematic approach must be implemented from class 1 to grade 6 in the learning process. It is important for elementary school teachers to be able to implement thematic approaches as professional responsibilities. This study aims to: 1) analyze elementary school teachers 'understanding of the thematic approach, 2) get the profile of elementary school teachers' ability in implementing thematic approaches, and 3) find out the constraints of teachers in implementing thematic approaches in elementary schools. The research used qualitative descriptive method with research subjects of grade 3 teachers in SD Negeri Tangerang 14. Data is collected by observation and interview. Triangulation is carried out through focus group discussions between researchers, teachers, and principals. The results of the study showed that the teacher understood the thematic approach well, but in practice 1 teachers studied did not carry out the thematic approach to learning. This study also revealed that most teachers experience obstacles in implementing thematic approaches to the learning process.